New sciaphilic plakinids (Porifera, Homoscleromorpha) from the Central-Western Pacific - Lage, Anaíra; Muricy, Guilherme; Ruiz, César; Pérez, Thierry (Zootaxa, 2018)
The sponge class Homoscleromorpha is a key model for the evolutionary biology of the Metazoa but its diversity remains poorly known. Here we describe six new species of the homoscleromorph family Plakinidae found in shaded habitats (submarine caves, tunnels and overhangs) of New Caledonia and Marquesas Islands, Central-Western Pacific. The new species belong to four genera: Corticium (Corticium vaceleti sp. nov.), Plakina (Plakina finispinata sp. nov.), Plakinastrella (Plakinastrella osculifera sp. nov., Plakinastrella nicoleae sp. nov. and Plakinastrella pseudolopha sp. nov.), and Plakortis (Plakortis ruetzleri sp. nov.). Plakinastrella pseudolopha sp. nov. has a novel spicule type called here ‘pseudolophose spicules’. The diversity of Homoscleromorpha is raised to 50 species in the Pacific Ocean and 120 spp. worldwide.